STRUKTUR POPULASI LABI-LABI (Amyda cartilaginea) DI DANAU ULAK KERAMAT KABUPATEN KAPUAS HULU - Sidit, Oktavianus; Soetignya, Widadi Padmarsari; Anzani, Yunita Magrima (Fakultas Pertanian Universitas Tanjungpura, 2025)
The Asiatic softshell turtle (Amyda cartilaginea) is a species of freshwater turtle that has been classified as vulnerable by the IUCN and inhabits rivers and lakes. Its utilization has been practiced for a long time, whether for food, traditional medicine, or as pets, which can disrupt the turtle's population. This study aims to examine the population structure, consisting of abundance and size distribution, growth patterns, sex ratio, and age structure, which can later serve as scientific information for conservation efforts. The research was conducted from July to August 2024 in Ulak Keramat Lake, Bika Subdistrict, Kapuas Hulu Regency. The data collected included curved carapace length (CCL), curved carapace width (CCW), weight, sex, and environmental conditions. Subsequently, the data were analyzed to determine abundance and size distribution, growth patterns, sex ratio, age structure, and diet. The study obtained 30 turtles with a CCL of 15